The economic burden of influenza-associated outpatient visits and hospitalizations in China: a retrospective survey - Juan Yang; Mark Jit; Kathy S. Leung; Ya-ming Zheng; Lu-zhao Feng; Li-ping Wang; Eric H. Y. Lau; Joseph T. Wu; Hong-jie Yu (Infectious Diseases of Poverty)
Abstract Background The seasonal influenza vaccine coverage rate in China is only 1.9 %. There is no information available on the economic burden of influenza-associated outpatient visits and hospitalizations at the national level, even though this kind of information is important for informing national-level immunization policy decision-making. Methods A retrospective telephone survey was conducted in 2013/14 to estimate the direct and indirect costs of seasonal influenza-associated outpatient visits and hospitalizations from a societal perspective. Study participants were laboratory-confirmed cases registered in the National Influenza-like Illness Surveillance Network and Severe Acute Respiratory Infections Sentinel Surveillance Network in China in 2013. Patient-reported costs from the survey were validated by a review of hospital accounts for a small sample of the inpatients. Results The study enrolled 529 outpatients (median age: eight years; interquartile range [IQR]: five to 20 years) and 254 inpatients (median age: four years; IQR: two to seven years). Among the outpatients, 22.1 % (117/529) had underlying diseases and among the inpatients, 52.8 % (134/254) had underlying diseases. The average total costs related to influenza-associated outpatient visits and inpatient visits were US$ 155 (standard deviation, SD US$ 122) and US$ 1,511 (SD US$ 1,465), respectively. Direct medical costs accounted for 45 and 69 % of the total costs related to influenza-associated outpatient and inpatient visits, respectively. For influenza outpatients, the mean cost per episode in children aged below five years (US$ 196) was higher than that in other age groups (US$ 129–153). For influenza inpatients, the mean cost per episode in adults aged over 60 years (US$ 2,735) was much higher than that in those aged below 60 years (US$ 1,417–1,621). Patients with underlying medical conditions had higher costs per episode than patients without underlying medical conditions (outpatients: US$ 186 vs. US$ 146; inpatients: US$ 1,800 vs. US$ 1,189). In the baseline analysis, inpatients reported costs were 18 % higher than those found in the accounts review (n = 38). Conclusion The economic burden of influenza-associated outpatient and inpatient visits in China is substantial, particularly for young children, the elderly, and patients with underlying medical conditions. More widespread influenza vaccination would likely alleviate the economic burden of patients. The actual impact and cost-effectiveness analysis of the influenza immunization program in China merits further investigation.